Isolation of a New Mexican Strain of Bacillus subtilis with Antifungal and Antibacterial Activities - M. G. L. Basurto-Cadena; M. Vázquez-Arista; J. García-Jiménez; R. Salcedo-Hernández; D. K. Bideshi; J. E. Barboza-Corona (The Scientific World Journal)
Although several strains of B. subtilis with antifungal activity have been isolated worldwide, to date there are no published reports regarding the isolation of a native B. subtilis strain from strawberry plants in Mexico. A native bacterium (Bacillus subtilis 21) demonstrated in vitro antagonistic activity against different plant pathogenic fungi. Under greenhouse conditions, it was shown that plants infected with Rhizoctonia solani and Fusarium verticillioides and treated with B. subtilis 21 produced augment in the number of leaves per plant and an increment in the length of healthy leaves in comparison with untreated plants. In addition, B. subtilis 21 showed activity against pathogenic bacteria. Secreted proteins by B. subtilis 21 were studied, detecting the presence of proteases and bacteriocin-like inhibitor substances that could be implicated in its antagonistic activity. Chitinases and zwittermicin production could not be detected. Then, B. subtilis 21 could potentially be used to control phytopathogenic fungi that infect strawberry plants.